Equine-assisted learning reduces anxiety and increases calmness and social skills in young people - Kezia Sullivan; Ann Hemingway (Academia Mental Health & Well-Being)
Since the COVID-19 pandemic, referrals to equine-assisted services (EAS) have increased, with a majority of referrals focusing on social, mental, and emotional health, and anxiety frequently included as a referral reason. Early intervention could help prevent ongoing health concerns from untreated anxiety disorders; this quantitative before and after measures study evaluates an equine-assisted learning program involved in developing positive social and coping skills in participants with anxiety. Participants with anxiety aged between 8 and 18 were referred to the program (n = 166), and referrers rated their skills on eight attributes at referral and at a 2-month follow-up after the program, which consisted of 5 × 2 h sessions of learning natural horsemanship groundwork. Significant improvements across all eight attributes at post-test, as well as the total score for all attributes combined (p < 0.001), were observed. The eight attributes were assertiveness, focus, responsibility, empathy, calmness, planning, communication, and engagement in learning. There was a significant interaction between Time and Age for Planning and Empathy attributes, suggesting that early adolescence (ages 11–14) is a key period for providing early interventions for skill development, which may help reduce anxiety in other contexts.